Neuromuscular and Mobility Responses to a Vibration Session in Hypoxia in Multiple Sclerosis - Andreu-Caravaca, Luis; Chung, Linda H.; Ramos-Campo, Domingo Jesús; Marín-Cascales, Elena; Encarnación-Martínez, Alberto; Rubio-Arias, Jacobo Á (International Journal of Sports Medicine, 2020)
The aim of this study was to investigate the acute effects of vibration training (WBVT) under hypoxic and normoxic conditions on the voluntary rate of force development (RFD), balance and muscle oxygen saturation (SMO2) in persons with Multiple Sclerosis (MS). 10 participants completed the study (30% males, 44.4±7.7 years, 164.3±8.9 cm, 65.2±11.1 kg, 2.5±1.3 Expanded Disability Status Scale, 24.1±4.0 kg.m−2 BMI). Maximal force, RFD during isometric knee extension, static balance with eyes open and closed and sit-to-stand test were evaluated before and immediately after one session of WBVT (12 60-s bout of vibration; frequency 35 Hz; amplitude 4 mm; 1-min rest intervals) under both normoxic and hypoxic conditions. In addition, SMO2 of the gastrocnemius lateralis was assessed during each condition. No changes were found in force, static balance and sit-to-stand test. Time-to-peak RFD increased in the left leg (p=0.02) and tended to increase in the right leg (p=0.06) after the hypoxic session. SMO2 resulted in significant increases from the initial to final intervals of the WBVT under both hypoxic and normoxic conditions (p<0.05). Increases in SMO2 during WBVT demonstrates muscle work that may contribute to the observed muscle adaptations in long-term WBVT programs without inducing decreases in neuromuscular activation, physical function and balance within a session.
Keywords: vibration training; neurological disorders; strength; muscle oxygenation; functional capacity